1979
DOI: 10.1111/j.1600-0447.1979.tb06942.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive scales for parasuicide repetition. Further results

Abstract: A six-item predictive scale for parasuicide repetition was retested on a second sample of Italian parasuicides. All the patients firstever admitted after a deliberate self-harm to the psychiatric department of a general hospital during the period April 1973-March 1976 were interviewed and followed-up after an interval of 1 year. The scale showed the same predictive power found in the first sample (1970-73) and gave a range of probability of repetition within 1 year of 15% at a score of 0 up to 44.8% at the sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
7

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 14 publications
0
9
0
7
Order By: Relevance
“…The validity of the scale was examined in six subsequent studies. The sensitivity of the scale tends to be high, falling above 80%, but its specificity is medium, falling between 56% and 67% [12], [40], [42], [64]. Two studies used a score on the scale as a continuous variable and found significantly increased risk of repetition with higher scores [23], [65].…”
Section: Resultsmentioning
confidence: 99%
“…The validity of the scale was examined in six subsequent studies. The sensitivity of the scale tends to be high, falling above 80%, but its specificity is medium, falling between 56% and 67% [12], [40], [42], [64]. Two studies used a score on the scale as a continuous variable and found significantly increased risk of repetition with higher scores [23], [65].…”
Section: Resultsmentioning
confidence: 99%
“…Some used prospective designs to delineate risk factors, and others identified variables in a study sample and tested these variables in a validation sample (Bagley & Greer, 1971; Buglass & Horton, 1974; Buglass & McCulloch, 1970; Kreitman & Foster, 1991). Some of these scales were subsequently cross‐validated in other clinical populations (Buglass & Horton, 1974; Garzotto, Siani, Tansella, & Tansella, 1976; Hawton & Fagg, 1995; Myers, 1988; Siani, Garzotto, Tansella, & Tansella, 1979). Only a few studies have used multivariate analyses (Bagley & Greer, 1971; Carter et al, 1999; Corcoran et al, 1997; Hjelmeland, 1996).…”
mentioning
confidence: 99%
“…However, the same scale was also tested on two Italian samples of parasuicide patients (Garzotto et al 1976;Siani et al 1979). Although in both cases the probability scores were similar to those obtained by Buglass & Horton, other social and clinical features appeared to discriminate better between repeaters and non-repeaters (Garzotto et al 1976), including one item -previous parasuicide not leading to admission -which was the opposite of one in the original list.…”
Section: From Correlation To Formal Predictionmentioning
confidence: 99%